Manfaat gerakan shalat bagi Kesehatan tubuh manusia: Analisis manfaat shalat bagi kesehatan rohani dan jasmani - Trisnawati, Fidian (Maliki Interdisciplinary Journal, 2025)
Prayer in language means prayer, in terms of sharia it is words and actions that begin with takbir and end with greetings with predetermined conditions. In addition to being a pillar of religion, prayer also has good benefits for a person's health in every movement. In addition to being spiritually beneficial, the movements in prayer also have a positive impact on physical health. Prayer movements have benefits for spiritual and physical health. Benefits for spiritual health, for example, prevent mental disorders, heal the mind and soothe the heart. While the benefits for physical health are in each prayer movement, one example is during the takbiratul ihram movement, this movement is useful for smoothing blood flow, lymph (lymph), and increasing arm muscle strength. This study uses a systematic approach method that aims to analyze the benefits of prayer movements on human spiritual and physical health. This study was conducted by collecting and reviewing relevant literature, both from journals and religious sources.